STRATEGI PENGELOLAAN ADMINISTRASI DALAM PENINGKATAN MUTU LEMBAGA PENDIDIKAN - Aisyah Nur Cahaya; Abdullah Aminuddin Aziz (Jurnal Publikasi Manajemen Informatika, 2025)
Administrative management strategies play a crucial role in improving the quality of educational institutions. Educational institutions are required to build optimal performance through professional and structured quality management. This study aims to describe the administrative management strategies, institutional quality, and the relationship between both in improving the quality of MTs. Salafiyah Syafi’iyah Tebuireng Jombang. This research employs a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation, while data analysis involves data reduction, data display, and conclusion drawing, with data validity ensured through source, time, and technique triangulation. The findings reveal that administrative management strategies are implemented through careful planning, clear organization, implementation that enhances human resource competencies, and continuous supervision. Institutional quality is achieved by aligning educational services with the needs and expectations of the community. Administrative management strategies contribute to institutional quality improvement through structured administrative practices and a continuous quality improvement cycle, aimed at delivering high-quality education services and producing competitive graduates.